Identification and Description of Aquatic Oligochaeta in Sanggau City Canal West Kalimantan - Galuh Ramadhanti; Erwinda (Jurusan Biologi Universitas Negeri Makassar, 2023)
The canal, which is located in the center of Sanggau City, West Kalimantan, is a channel for water to flow directlyinto the Kapuas River. The dense activity of the surrounding community has caused indications of contaminationof this canal by organic and inorganic materials. Pollutants enter continuously and accumulate, thereby changingthe structure of the substrate which becomes a habitat for benthic fauna such as aquatic Oligochaeta. This studyaims to identify and describe the types of aquatic Oligochaeta found in the canals of Sanggau City. This researchwas conducted in August-September 2020 using a purposive sampling technique. Sampling locations were carriedout at five stations consisting of Tanjung Sekayam Village, Ilir Kota Village, Beringin Village and Bunut Village.The Sanggau City Canal has a depth ranging from 0. 24 m – 1 m with water brightness 0.14 m – 0.24 m. The canalwhich is a lotic water also has a current velocity range of 0.04 m/s – 0.40 m/s with a temperature of 27°C – 29°Cand pH 6.0 – 6.7. Dissolved oxygen in the canals of Sanggau City which plays an important role in the survival ofaquatic Oligochaeta is obtained 3.0 mg/l – 5.8 mg/l, and C-Organic 0.05% - 3.82%. The substrate in the canal ofSanggau City is composed of 23.31% - 95.31% sand, 4.69% - 57.49% silt and 0.00% - 19.20% clay.Each samplingstation consists of three repetition points. Based on the results of research conducted on five canals in SanggauCity, aquatic Oligochaeta were found consisting of 1 order, 1 family, 2 genera and 3 species with a total of 1367individual aquatic Oligochaeta. The identified aquatic Oligochaeta species consisted of B. sowerbyi, L.claparedeianus, and L. hoffmeisteri.